2014
DOI: 10.1007/s00438-014-0914-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of retrotransposons and assessment of genetic variability based on developed retrotransposon-based insertion polymorphism (RBIP) markers in Pyrus L

Abstract: Interspecific hybridization has been considered the major mode of evolution in Pyrus (pear), and thus, the genetic relationships within this genus have not been well documented. Retrotransposons are ubiquitous components of plant genomes and 42.4 % of the pear genome was reported to be long terminal repeat (LTR) retrotransposons, implying that retrotransposons might be significant in the evolution of Pyrus. In this study, 1,836 putative full-length LTR retrotransposons were isolated and 196 retrotransposon-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…In this study, we identified predicted LTR-retrotransposons in the ‘Suli’ genome, and focused on LTR-retrotransposons that had the highest likelihood of being functional based on the presence of annotated inner protein domains. Previously, we identified 1836 retrotransposons by running LTR-harvest based on two nearly sister LTR flanking sequences and some conserved sequence motifs [ 27 ]. However, the current study showed that only 440 retrotransposons had at least two inner protein domains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we identified predicted LTR-retrotransposons in the ‘Suli’ genome, and focused on LTR-retrotransposons that had the highest likelihood of being functional based on the presence of annotated inner protein domains. Previously, we identified 1836 retrotransposons by running LTR-harvest based on two nearly sister LTR flanking sequences and some conserved sequence motifs [ 27 ]. However, the current study showed that only 440 retrotransposons had at least two inner protein domains.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, 1836 full-length LTR-retrotransposons were mined from the whole-genome data of Pyrus (AJSU00000000) [ 27 ]. The details of each retrotransposon were obtained from the output of LTRharvest.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A marker from any of the anonymous multilocus RTE-based applications can be modified into an equivalent retrotransposon-based insertion polymorphism marker (Fig. 2) and vice versa (Jing et al 2010, Jiang et al 2015. Markers from the former methods are straightforward to harvest and can be rapidly analysed for their informativeness before investing in the advancement of a matching retrotransposon-based insertion polymorphism marker.…”
Section: Use Of Rtes To Investigate Genetic Variability In Plantsmentioning
confidence: 99%